Deep‐Blue Phosphorescent Ir(III) Complexes with Light‐Harvesting Functional Moieties for Efficient Blue and White PhOLEDs in Solution‐Process. (16th May 2017) - Sarada, Ganguri; Cho, Woosum; Maheshwaran, Athithan; Sree, Vijaya Gopalan; Park, Ho‐Yeol; Gal, Yeong‐Soon; Song, Myungkwan; Jin, Sung‐Ho
Abstract : The photoluminescence (PL) efficiency of emitters is a key parameter to accomplish high electroluminescent performance in phosphorescent organic light‐emitting diodes (PhOLEDs). With the aim of enhancing the PL efficiency, this study designs deep‐blue emitting heteroleptic Ir(III) complexes (tBuCN‐FIrpic, tBuCN‐FIrpic‐OXD, and tBuCN‐FIrpic‐mCP) for solution‐processed PhOLEDs by covalently attaching the light‐harvesting functional moieties (mCP‐Me or OXD‐Me) to the control Ir(III) complex, tBuCN‐FIrpic. These Ir(III) complexes show similar deep‐blue emission peaks around 453, 480 nm (298 K) and 447, 477 nm (77 K) in chloroform. tBuCN‐FIrpic‐mCP demonstrates higher light‐harvesting efficiency (142%) than tBuCN‐FIrpic‐OXD (112%), relative to that of tBuCN‐FIrpic (100%), due to an efficient intramolecular energy transfer from the mCP group to the Ir(III) complex. Accordingly, the monochromatic PhOLEDs of tBuCN‐FIrpic‐mCP show higher external quantum efficiency (EQE) of 18.2% with one of the best blue coordinates (0.14, 0.18) in solution‐processing technology. Additionally, the two‐component (deep‐blue:yellow‐orange), single emitting layer, white PhOLED of tBuCN‐FIrpic‐mCP shows a maximum EQE of 20.6% and superior color quality (color rendering index (CRI) = 78, Commission Internationale de L'Eclairage (CIE) coordinates of (0.353, 0.352)) compared with the control device containing sky‐blue:yellow‐orange emitters (CRI = 60, CIE coordinates of (0.293, 0.395)) due to the good spectral coverage by the deep‐blue emitter. Abstract : Highly efficient deep ‐blue phosphorescent Ir(III) complexes with light‐harvesting groups are introduced for blue and white phosphorescent organic light‐emitting diodes. Intramolecular energy transfer from a high triplet energy donor (mCP‐Me) to the Ir(III) complex (tBuCN‐FIrpic) is found to increase the photoluminescence efficiency of tBuCN‐FIrpic‐mCP. Therefore, tBuCN‐FIrpic‐mCP shows high external quantum efficiency of 18.2% with intense blue coordinates (0.142, 0.181) in a solution‐process.